Thermal behaviour and thermodegradation Kinetics of Poly(Vinyl Chloride) Plasticized with Polymeric and Oligomeric Medium-Chain-Length Poly(3-hydroxyalkanoates) - Sin, M.C.; Tan, I.K.P.; Annuar, M.S.M.; Gan, S.N. (2012)
Poly(vinyl chloride) (PVC) is a well-known polymer with low thermal stability. With the aim to improve the physical properties of PVC, biopolyesters were investigated for the plasticizing and thermal effects in PVC. In this study, polymeric medium-chain-length poly(3-hydroxyalkanoates) (mcl-PHA) were produced by Pseudomonas putida PGA1 using renewable carbon substrates and oligomeric mcl-PHA were generated by partial thermal degradation of the polymers. The effects of blending these biopolyesters with PVC were investigated in terms of thermal behaviour and thermodegradation kinetics. The PVC/PHA blends showed a single Tg with lower values than PVC, indicating that mcl-PHA was compatible with PVC. Tg from DSC analysis agreed well with theoretical Tg predicted from GordonâTaylor equation. The apparent activation energy (Ed) and pre-exponential factor (A) for the thermodegradation of PVC and its blends were determined using Kissinger method. Change in entropy of activation (ÎS) for the thermodegradation was also determined. All PVC/PHA blends had lower Ed, A and ÎS than PVC. Higher reduction of Ed, A and ÎS was observed when the proportion of PHA was increased in the blend; and when oligomeric PHA was used as the plasticizer instead of polymeric PHA. The dependence of Ed on the extentÂ of conversion (Î±) for the thermodegradation process of PVC and PVC/PHA was determined by FlynnâWallâOzawa method and results showed that Ed is an increasing function of Î±. This indicated that the thermal decomposition of PVC and its blends display complex reaction mechanism(s).